2005
DOI: 10.1152/ajpregu.00443.2004
|View full text |Cite
|
Sign up to set email alerts
|

Salinity acclimation affects the somatotropic axis in rainbow trout

Abstract: In this study, we set out to examine the role of the somatotropic axis in the ion-regulation process in rainbow trout. Specifically, our objective was to examine whether plasma insulin-like growth factor-binding proteins (IGFBPs) are modulated by gradual salinity exposure. To this end, freshwater (FW)-adapted rainbow trout were subjected to gradual salinity increases, up to 66% seawater, over a period of 5 days. During this acclimation process, minimal elevations in plasma Ca 2ϩ and Cl Ϫ were seen in the salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 91 publications
(194 reference statements)
2
32
1
Order By: Relevance
“…Similar to the transgenic fish, we found modulation of the complement factor genes, CCAAT/enhancer-binding protein, and barrier-to-autointegration factor genes via microarray. These are in agreement with previous studies that observed increased immune stimulation following GH administration (4) or seawater acclimation, in which endogenous GH is typically elevated (56,66). However, in the present study, we have also identified immune-related genes that that were not differentially expressed in the GH transgenic fish, indicating a difference in the response between the short-term and long-term effects of GH on the immune system.…”
Section: Rainbow Trout Gh Microarray Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to the transgenic fish, we found modulation of the complement factor genes, CCAAT/enhancer-binding protein, and barrier-to-autointegration factor genes via microarray. These are in agreement with previous studies that observed increased immune stimulation following GH administration (4) or seawater acclimation, in which endogenous GH is typically elevated (56,66). However, in the present study, we have also identified immune-related genes that that were not differentially expressed in the GH transgenic fish, indicating a difference in the response between the short-term and long-term effects of GH on the immune system.…”
Section: Rainbow Trout Gh Microarray Analysissupporting
confidence: 93%
“…Neither the transcript identity nor the mechanisms of GHBP formation have been reported in the rainbow trout. However, during saltwater acclimation in the rainbow trout, which is characterized by a significant increase in GH secretion (56), serum GHBP was found to increase significantly (62). Here we provide evidence for regulation of GHR or GHBP in fish similar to that indicated in mammalian species.…”
Section: Rainbow Trout Gh Microarray Analysismentioning
confidence: 99%
“…This process is associated with increased hepatic expression of IGF-I mRNA (29) and circulating IGF-I (1), suggesting a hypoosmoregulatory role of the hormone. On the other hand, direct transfer of rainbow trout to 80% SW induced no change in liver IGF-I mRNA levels (28), whereas acclimation to 66% SW induced a gradual increase in circulating IGF-I levels over 5 days (33). More conclusive evidence for the role of IGF-I as a SW-adaptive hormone in salmonids (rainbow trout, 18; Atlantic salmon, 19; brown trout, 30) is offered by injection experiments in which IGF-I improves hypoosmoregulatory ability.…”
Section: Discussionmentioning
confidence: 93%
“…Further, the zebrafish IGFBP-1 promoter contains a functional hypoxia-response element, indicating that cellular pathways for direct hypoxia induction of IGFBP-1 exist in fishes (Kajimura et al 2006). A 21 kDA IGFBP increased during gradual seawater adaptation in rainbow trout; however, cortisol increased only slightly and transiently (Shepherd et al 2005). Further studies are required to evaluate the role of cortisol in the regulation of fish IGFBP-1 by various physiological stressors.…”
Section: Discussionmentioning
confidence: 99%